High-velocity impact resistance of doubly curved sandwich panels with re-entrant honeycomb and foam core - Usta, Fatih; Türkmen, Halit S.; Scarpa, Fabrizio (International journal of impact engineering, 2022)
•High-velocity impact resistance of doubly curved CFRP sandwich panels is presented.•Impact tests are carried out by using a single-stage air gas gun test machine.•An analytical model is developed to describe the ballistic limit velocity.•Parametric analyses are carried out for various radius of curvature of the panels. This work describes the high-velocity impact behavior of doubly curved sandwich panels. The sandwich panels are manufactured using carbon/fiber epoxy composite face sheets, polyurethane foam core and 3D-printed PLA plastic cellular auxetic (re-entrant) honeycombs. High-velocity impact tests are carried out by using a single-stage air gas gun test machine. A spherical steel projectile with the radius of 5 mm is impacted to the center of the specimens with the speed of 100 m/s. The experimental data are used to validate explicit finite element models of the doubly curved structures. An analytical model is also developed for the ballistic limit of the flat and doubly curved sandwich panels, and the analytical results are compared to those obtained from the numerical ones. Parametric numerical analyses of the high-speed impact of the curved sandwich panels are then carried out considering various radii of curvature of the panels. The results show that the energy absorption is increased as the curvature is decreased for the panels with both foam and re-entrant core. In addition, the core configuration provides a key role in the impact resistance of the sandwich panels. Re-entrant models show an increase in specific energy absorption (SEA) compared to the foam core types. [Display omitted]